2021
DOI: 10.3390/genes12040501
|View full text |Cite
|
Sign up to set email alerts
|

Chances and Challenges of New Genetic Screening Technologies (NIPT) in Prenatal Medicine from a Clinical Perspective: A Narrative Review

Abstract: In 1959, 63 years after the death of John Langdon Down, Jérôme Lejeune discovered trisomy 21 as the genetic reason for Down syndrome. Screening for Down syndrome has been applied since the 1960s by using maternal age as the risk parameter. Since then, several advances have been made. First trimester screening, combining maternal age, maternal serum parameters and ultrasound findings, emerged in the 1990s with a detection rate (DR) of around 90–95% and a false positive rate (FPR) of around 5%, also looking for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 110 publications
2
47
0
Order By: Relevance
“…There are many methods for screening for trisomy 21, trisomy 18, and trisomy 13, including maternal serum screening (MSS), ultrasound, and noninvasive prenatal testing (NIPT) ( 4 ). In contrast, limited methods can be used to screen SCAs, as the clinical features of most SCAs are not detectable during prenatal ultrasound examination because many develop after birth with the exception of structural anomalies more commonly seen in the Turner syndrome ( 1 , 5 7 ). With the discovery of circulating cell-free fetal DNA (cffDNA) in the blood samples of pregnant women and the advent of massively parallel genomic sequencing (MPS) technology, NIPT has been widely applied for the clinical screening for fetal chromosomal aberrations and has already expanded beyond the three common autosomal trisomies to include SCAs ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are many methods for screening for trisomy 21, trisomy 18, and trisomy 13, including maternal serum screening (MSS), ultrasound, and noninvasive prenatal testing (NIPT) ( 4 ). In contrast, limited methods can be used to screen SCAs, as the clinical features of most SCAs are not detectable during prenatal ultrasound examination because many develop after birth with the exception of structural anomalies more commonly seen in the Turner syndrome ( 1 , 5 7 ). With the discovery of circulating cell-free fetal DNA (cffDNA) in the blood samples of pregnant women and the advent of massively parallel genomic sequencing (MPS) technology, NIPT has been widely applied for the clinical screening for fetal chromosomal aberrations and has already expanded beyond the three common autosomal trisomies to include SCAs ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Germany, the debate on reproductive autonomy in the context of NIPT often focuses on the woman’s right not to know’ or her right to decline available prenatal tests [ 27 – 29 ]. It is also suggested that, in addition to information provided by professionals, a woman should be put in contact with associations or families who have a child living with a trisomy [ 6 , 30 ], so, she is able to make a fully informed decision about whether to continue or terminate her pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…Fetal DNA analysis is the only method for detecting these disorders. The correlation between an elevated risk for pathological copy number variations and increased nuchal translucency, as well as altered serum levels of PAPP-A and free β-HCG, was noticed [ 1 , 2 ]. Other than these, the main indications for wide NIPT analysis are previous children with chromosomal alterations, the sonographic detection of fetal abnormalities, and a history of family members testing positive for chromosomal or genetic disorders [ 3 ].…”
Section: Introductionmentioning
confidence: 99%